In vitro characterization and transfection of IL-2 gene complexes - (:unkn) unknown (ELSEVIER, 2006)
Background: Interleukin-2 used in the treatment of malignant tumors has an anti-tumor efficacy. In this study, we have studied in vitro characterization and transfection efficiency of a plasmid encoding hIL-2, pCXWN-hIL-2, complexed to chitosan, polyethylenimine or DOTAP with varying ratios. Methods: Plasmid DNA was amplified in Escherichia coli DH5 alpha and isolated by alkali lysis method. The pDNA/chitosan, pDNA/PEI or pDNA/DOTAP complexes were analyzed by agarose gel electrophoresis for complex formation and by ESEM image analysis system for the morphology and DNA/medium relationship of complexes. DNase stability, the particle size and zeta potential values of complexes were determined. Transfection efficiencies of resulting complexes in two different cell lines were assayed by ELISA method. Results: Conclusively, a transfection activity was observed in both cell lines (HeLa and Swiss3T3) with the order of pDNA/DOTAP > pDNA/PEI > pDNA/chitosan complexes. We have observed that the transfection efficiency was higher in HeLa cell line compared to Swiss3T3 cell line. Conclusion: The physicochemical studies like stability, particle size and zeta potential, showed a relationship between the properties of a complex and its transfection efficiency. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: interleukin-2; chitosan; polyethylenimine; DOTAP; gene delivery; non-viral; LOW-MOLECULAR-WEIGHT; DELIVERY-SYSTEM; NONVIRAL VECTOR; DNA DELIVERY; CHITOSAN; POLYETHYLENIMINE; EFFICIENCY; PLASMID; POLYPLEXES; EXPRESSION